انتشار الفساد في ظل حكم ثورة الانقاذ الوطني : أسبابه و أشكاله وآثاره وجهود مكافحته في السودان: The Causes of corruption under the rule of the National Salvation Revolution: its forms and Impacts and combating Efforts in Sudan - Ahmed Mohamed, Ahmedin Salih; Abdelsalam, Elfatih Abdallah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
يدرس هذا المقال ظاهرة تفشي الفساد في عهد حكم ثورة الانقاذ الوطني في السودان، أسبابه وأشكاله وأثاره، والسؤال الجوهري الذي انطلقت منه الدراسة هو: ما أسباب الفساد في السودان في ظل الانقاذ الوطني رغم وجود مؤسسات مكافحته؟ وما أشكاله وآثاره؟ ويتناوله من خلال المنهج الوصفي النوعي والتحليلي ، وعبر تحليل المعلومات المتوفرة توصل إلى أن الفساد انتشر على نطاق واسع في عهد ثورة الانقاذ الوطني في السودان بالرغم من وجود قوانين ومؤسسات مكافحة الفساد، كماخلص إلى أنّ هناك أسبابًا متعدة لتفشيه، من أظهرها ضعف الرقابة المتبادلة بين السلطات التشريعية والتنفيذية لغياب السلطة التشريعية لفترة طويلة من حكمها، فكرس ذلك لهيمنة السلطة التنفيذية فضلا عن ضعف الإرادة السياسية لدى القيادة، والسياسات الخاطئة التي اعتمدها النظام، وكان لانتشاره آثاراً سلبية اقتصادية بإحداث خلل في توزيع الثروة بالعدل، واجتماعية باثارة الغبن والظلم لدى بعض فئات المجتمع ، الذي أدى لإثارة الحروب وعدم الاستقرار في البلاد، ومن ثم توصي الدراسة بضرورة تعزيز الإرادة السياسية وإصلاح التشريعات والمؤسسات التي تضطلع بمحاربة الفساد. This article examines the phenomenon of spreading of corruption during the rule of the National Salvation Revolution in Sudan, its causes, forms and sequences, and the fundamental question from which the study was launched was that, what are the causes of corruption in Sudan during the rule of salvation revolution, even with the existence of the anti-corruption institutions? And what are the forms and impacts? In examining this issue, uses a descriptive qualitative and analytical approach, and through analyzing the available data, the article concluded that corruption has widely spread during the era of the National Salvation Revolution in Sudan despite the existence of anti-corruption laws and institutions. It also concluded that there are multiple reasons for its spread. Among them lack of check and balance syetm and mutual control of the legislation and executive authorities due to the absence of the legislative authority for a long period, which devoted to the dominance of the executive authority, as well as weak of political will, and as a result of its spread there were negative economic impacts by causing an imbalance in the distribution of wealth in justice and socially by stirring up a sense of injustice in Some groups of society, which have led to war and instability in the country, and then the study recommends to combating corruption effectively need to strengthening the political will, and reforming anti-corruption legislations and institutions that help in fighting agaist corruption.